Dinamika Pengaruh Keseimbangan Kerja, Beban Kerja, dan Stres Terhadap Kejenuhan Pada Pegawai BPS - Dwi Kartika, Yulia; Suratno, Eddy; Paul Karolus Pasaribu, Johni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The purpose of this study is to examine the effect between burnout in Jambi Province BPS employees and work-life balance, workload, and work stress. In this study, data is gathered quantitatively through the use of Google Forms to disseminate surveys. Using census or saturation sampling as a sampling approach, the 72 employees of BPS Jambi Province made up the sample under study. Using SPSS version 25, several mutliple linear regression analysis approaches were used to the research data. The variables of workload, work-life balance, and work stress have a significant impact on employee burnout in Jambi Province BPS, both partially and simultaneously, according to the data.